Comparação entre as vias intranasal e intramuscular para a imunização com uma vacina de antígeno bruto de Staphylococcus aureus - Stegmiller, Nataly Pescinalli (2014)
Mastitis is a disease of the mammary gland characterized by an inflammatory process, often due to the infectious microorganisms presence. It is considered the main cause of economic losses related to dairy practice, as it can act directly in the organ function, decreasing to 15-20% milk/animal production. Among the microorganisms identified as causing the mastitis, Staphylococcus aureus bacteria species are the most common, accounting for over 91% of mastitis cases. The emergence of drug-resistant strains associated with high toxicity of the treatment, prints the need to develop an effective, inexpensive and safe vaccine that could be used as a preventive measure against mastitis. In this work, we aimed to develop a vaccine produced with total antigen of S. aureus (SaAg) and intranasaly or intramuscularly given against experimental mastitis. The vaccine preparation was done using a S. aureus strain isolated from bovine mammary gland, followed of 15 slow freezing /thawing cycles. BALB/c mice were vaccinated by intranasal or intramuscular route with 2 doses of SaAg (50μg/animal) followed of biocompatibility and immunogenicity evaluation 72 hours after each dose. Intramuscular vaccinated mice showed behavioral and physical changes. No differences of transaminases and creatinine levels were observed in the vaccinated groups as compared to unvaccinated animals, different from observed in the lymphoproliferative responses. Intranasal vaccinated mice presented significant percentage increase of CD4+ and CD8+ IFN-γ producer’s when compared to intramuscular or unvaccinated groups. By the other hand, mice vaccinated by intramuscular route showed a increase of CD4+ and CD8+ T cells producers percentage also supernatant cytokine production (Il-10 and IFN- γ) after SaAg in vitro recall, when compared to intramuscular vaccinated animals or unvaccinated. The Intranasal vaccination induced a significant increase of IgG2a levels and decreased IgG1 production when compared to control or intramuscular vaccinated groups. Thus, our results demonstrate the feasibility of SaAg vaccine, given by intramuscular and intranasal routes, as a potential prophylactic agent against mastitis caused by S. aureus.